A review of Debswana's performance pre and post the acquisition of De Beers shares by Anglo American plc - Mothulatshipi, Khumo (My University, 2016)
The minerals industry has in the last decade witnessed volatility, uncertainty, complexity and ambiguity (VUCA). The diamond industry has not been immune to these challenges. These challenges coincided with the decision of the diamond mining family in 2011 to opt out of De Beers after approximately a century of being in control by selling their 40 % stake to Anglo American plc (AA) which already had 45 % stake in De Beers. This transaction increased Anglo American plc‟s stake in De Beers to 85% thus joining venture with the Government of the Republic of Botswana (GRB) under an already existing entity called Debswana. Botswana has been hailed as a beacon of success and a model African state both politically and economically mainly due to its effective management of economic proceeds generated mainly through Debswana diamonds. Something that might be seen as a possible threat to this economic stability is the merger and acquisition (M&A) between the GRB and AA. As a result this study was conducted as a way of investigating any possible impacts of the partnership of GRB and AA on the Debswana diamond company through the M&A transaction that occurred in 2011. The study was restricted to the mining operations in order to assess Debswana‟s performance more meaningfully pre and post the acquisition of De Beers shares by AA. The mining activities from Debswana operations comprise of Letlhakane, Damtshaa, Orapa, Jwaneng and Morupule Coal mine. The study is focusing on the production statistics and financial analysis using stock market and financial ratios. These are discussed in detail to assess the possible impact of the merger on Debswana‟s performance. In addition to this, empirical evidence based on factors determining a firm‟s performance before and after acquisition or merger is also discussed, with further action of aligning determinants to the literature findings. The study‟s key findings were that there has been a significant reduction in AA‟s financial performance post-merger but Debswana‟s performance has been fairly consistent. This is probably due to the fact that the 3-year post merger window period may not be sufficient to observe sufficient changes in Debswana‟s performance. Further research can be conducted on the current AA‟s repositioning strategy that aims at divesting in other operations and focusing on others and its impact on Debswana over a much longer window period than 3 years.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Science in Engineering. Johannesburg, 2015
Keywords: De Beers Botswana Mining Company; Consolidation and merger of corporations; Mineral industries--Mergers; Mining corporations; Corporations--Valuation